Family association study between INSR gene polymorphisms and PCOS in Han Chinese - Chen Zi-Jiang; Zhao Yueran; Bian Yuehong; You Li; Shi Yuhua; Zhao Han; Xu Xinghua (BMC, 2011)
Abstract Background Polycystic ovary syndrome (PCOS) is a complex disease having both genetic and environmental components. Candidate genes with insulin metabolism have been hypothesized to be involved in the etiology of this syndrome. In the present study, we investigated the genetic association between polymorphisms in the insulin receptor (INSR) gene and PCOS. Methods A total of 260 family trios were recruited and performed a family-based analysis to assess linkage and association between four single nucleotide polymorphisms (SNPs) (rs1799817, rs2059807, rs8108622 and rs10500204) of INSR gene and PCOS. Results Using the transmission disequilibrium test (TDT), we failed to find that rs1799817 (p = 0.486), rs2059807 (p = 0.195), rs8108622 (p = 0.866) and rs10500204 (p = 1.0) were significantly overtransmitted to PCOS offspring from their parents. Conclusion No significant evidence of association or linkage was found in the four tested markers, indicating that our family samples did not support susceptibility of the INSR gene to PCOS.